Calcule o f (3) +f (8) -f (5) de acordo com a lei da função f(x)=4x/2 +9.
Soluções para a tarefa
Respondido por
0
Resposta: 16.
Explicação passo-a-passo:
f(x) = 4x/2 + 9
Substituindo o x pelo o número entre parênteses
f(3) = 4.3/2 + 9
f(3) = 12/2 + 9
f(3) = 6+9 ... f(3) = 15.
f(8) = 4.8/2 + 9
f(8) = 32/2 + 9
f(8) = 16 + 9 ... f(8) = 25.
f(5) = 4.5/2 + 9
f(5) = 20/2 + 9
f(5) = 10 + 9 ... f(5) = 19.
f(3) + f(8) - f(5) =
15 + 25 - 19
35 - 19 =16.
Perguntas interessantes
Geografia,
10 meses atrás
Português,
10 meses atrás
Matemática,
1 ano atrás
Química,
1 ano atrás
Matemática,
1 ano atrás
Inglês,
1 ano atrás
Administração,
1 ano atrás